Strategies of Survival: The Well-being of Builsa Women in the Upper East Region of Northern Ghana. - Abbey, Eunice (Advances in Social Sciences Research Journal, 2017)
The rural women in Northern Ghana face some persistent constraints that hamper their efforts to enjoy well-being. These have been linked to combined systems of patriarchy, socio-cultural values, environmental and economic issues. Whilst a lot of studies have been done on the challenges of the rural women in these areas, little is known on their ability to thrive in the midst of their numerous disadvantages. Inferring from the Community Capitals Framework by Flora and Flora (2013), this paper highlights some of the disadvantages encountered by the women whilst emphasizing the measures adopted to enhance their well-being. Using the qualitative research method, 20 women from two villages in the Upper East Region served as the participants. Data collection methods included in-depth interviews and Observation. The findings revealed the women were able to adopt means such as engaging in income generating activities, religion, harnessing resources from their natural capital amongst others to thrive regardless of their disadvantages.